1989
DOI: 10.1016/0266-7681(89)90127-7
|View full text |Cite
|
Sign up to set email alerts
|

Homodigital neurovascular island flaps for digital pulp loss

Abstract: Terminal amputations with loss of the distal pulp are common injuries. This report analyses 64 consecutive cases of advanced or exchanged homodigital neurovascular island flaps operated on by one surgeon between 1981-1986. The surgical technique, indications, contra-indications and five year results are evaluated. Overall, these flaps provide reliable vascularity as well as normal sensibility at the distal end of the finger where high quality perception is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
8

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 23 publications
3
48
0
8
Order By: Relevance
“…Using this flap, Foucher et al [15] reported 84 % of patients achieving sensation with two-point discrimination of 3-7 mm. In patients whose index fingers were treated, 12.5 % substituted the middle finger for fine pinch activities.…”
Section: Antegrade Homodigital Island Flapmentioning
confidence: 97%
“…Using this flap, Foucher et al [15] reported 84 % of patients achieving sensation with two-point discrimination of 3-7 mm. In patients whose index fingers were treated, 12.5 % substituted the middle finger for fine pinch activities.…”
Section: Antegrade Homodigital Island Flapmentioning
confidence: 97%
“…[1][2][3] This concept of reconstruction has definite advantages in meeting our goals of digital reconstruction. In particular, it reconstructs 'like with like' and avoids the creation of further scarring and morbidity elsewhere on the hand or body.…”
Section: Homodigital Reconstructionmentioning
confidence: 99%
“…Replacement of the radial side of the index or middle finger-tips by a vascularised composite transfer from the ulnar side of the same digit is well established, both as a simple transposition 31 and as an island flap. [2][3] Use of the radial pulp of the thumb tip to reconstruct and/or reinnervate the ulnar side would seem as logical and we recently reported three cases of this switch as a simple transposition flap (Figure 8). 32…”
Section: Reconstruction Of the Digital Tipmentioning
confidence: 99%
“…Opinions vary from the simplest conservative treatment [1,2] to the most sophisticated microsurgical reconstruction techniques, using various types of flaps [3][4][5][6][7][8][9]. Mouchet & Gilbert [10] described the use of the monopedicled volar neurovascular island flap in children and Foucher et al [11] reported their preliminary experience in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, surgery in the hand should aim at preservation of adequate and functional length of the digits, immediate coverage of the wound, preservation of sensibility at the distal pulp, adequate distal interphalangeal joint motion, a painless scar, short hospital stay and morbidity and early return to work and other daily activities [11,12]. In this study, I present the results of a large series of patients who were treated with homodigital neurovascular island flaps based on a single neurovascular pedicle to reconstruct amputated fingertips.…”
Section: Introductionmentioning
confidence: 99%